Pythagorean Fuzzy Weighted Averaging Aggregation Operator and its Application to Decision Making Theory - Rahman, K.; Ali, A.; Shakeel, M.; A. Khan, M. S.; Ullah, Murad (The Nucleus, 2017)
The objective of the present work is divided into two folds. Firstly, Pythagorean fuzzy weighted averaging aggregation operator has been introduced along with their several properties, namely idem potency, boundedness and monotonicity. Secondly, we apply this proposed operator to deal with multiple attribute group decision making problems under Pythagorean fuzzy information. For this we construct an algorithm for multiple attribute group decision making problems. At the last we also construct a numerical example for multiple attribute group decision making.